From Tech Novice to Tech Savvy – A Review on Hospitality Housekeeping - Chandana Paul, (European Economic Letters (EEL), 2024)
The hospitality industry is goingthrogh a profound change in terms of digitization, technology advancements and amenities. Each sector in hospitality industry whether its hotels, restaurants, hospitals, Multiplex etc, every sector is changing for the better with technology and digitization. The implementation of technology in hospitality industry is not new but this pandemic has acted as a catalyst in the rapid digital transformation even in the back of the house department like housekeeping Post covid there are many new practices and trends which includes sanitization, new cleaning protocols, Use of technology, Robot service, AI etc to enhance the experience of the customer and to benefit the employee’s working environment.